Revolução burguesa e ensino profissional: o protagonismo da Comissão Brasileiro-Americana de Educação Industrial (1946-1961) - Bordignon, Talita Francieli (Universidade Federal de São Carlos, 2018)
The present thesis aims to analyze the protagonism of the Brazilian-American Commission for Industrial Education (CBAI – Comissão Brasileiro Americana de Educação Industrial) in the substitution of imports in Brazil and the actions to promote bourgeois hegemony through industrial technical schools. The objects of analysis are the CBAI Bulletins, monthly periodicals published by the commission between 1947 and 1961. The historical development of the Brazilian society shows that the patrimonialism explains the interpermeation between the public and private spheres, where it is difficult to identify the subjects who compose the State and those who constitute the dominant classes. This study tried to identify the subjects who acted as agents of the Bourgeoisie Revolution in Brazil in this period and characterize the development of capitalism in the country as peripheral and autocratic, increasing social inequalities, as observed by Florestan Fernandes. In order to make itself hegemonic, the Brazilian bourgeoisie behaved as an organic intellectual, interested in destroying the possibilities of the implementation of a non-capitalist society and focused on solidifying the liberalism in all the spheres of collectivity. The Bourgeoisie Revolution agents acted organically and articulated with the international elites, operated the ideological inculcation of the American way of life, with values associated with the industrial liberal society, and the Americanism and Fordism led the whole process. The industrial technical education was the stage and the strategy the owners of the power used to operate their desire to maintain the bourgeois liberal order. John Dewey’s New School principles were spread in the industrial technical schools by the CBAI in order to root liberal society ideas in the workers’ mentality and daily lives, in an attempt to maintain the society organized into antagonist classes and avoid the order revolution. The unifying differentiation, as proposed by Émile Durkheim, was the method that consolidated the liberal democracy in a way to perpetuate the economic differences between individuals and those belonging to the bourgeoisie, the latter in their hegemonic position of owners, exploiting labor for capital accumulation. Moreover, soviet pedagogy principles are mentioned, placing labor as a pedagogical element, in order to understand the liberal counterpart and the bourgeoisie panic, along with their effort to design the superstructure. The research took the historical and dialectical materialism as theoretical and methodological referential and used analytical categories pertinent to the method, such as the notion of organic intellectual and the extended state according to Antonio Gramsci. In summary, the analysis aimed to understand the dialectic relation between the superstructure conformation – search for consensus – to control the infrastructure and production relations, preventing the working classes from taking power.
Bourgeoisie revolution and technical education: the protagonism of the Brazilian-American Commission for Industrial Education (1946-1961)
Keywords: Ensino técnico industrial; Revolução burguesa; Escola nova; Intelectuais orgânicos; Comissão Brasileiro-Americana de Educação Industrial; Industrial technical education; Bourgeoisie revolution; Organic intellectuals; New school; CIENCIAS HUMANAS::EDUCACAO::FUNDAMENTOS DA EDUCACAO::FILOSOFIA DA EDUCACAO; CIENCIAS HUMANAS::EDUCACAO::FUNDAMENTOS DA EDUCACAO::HISTORIA DA EDUCACAO; CIENCIAS HUMANAS::EDUCACAO::FUNDAMENTOS DA EDUCACAO::SOCIOLOGIA DA EDUCACAO